Short term hypoxia synergizes with interleukin 15 priming in driving glycolytic gene transcription and supports human natural killer cell activities - Velásquez, Sonia Y.; Schulte, Jutta; Sticht, Carsten; Thiel, Manfred; Lindner, Holger A. (The journal of biological chemistry, 2016)
Natural killer (NK) cells induce apoptosis in infected and transformed cells and are important producers of immunoregulatory cytokines. Therefore, they operate under low oxygen conditions (hypoxia) in inflammatory and tumor environments. In vitro studies of NK cells are, however, commonly performed in ambient air (normoxia). We used global gene expression profiling to evaluate changes in transcriptional pathways in primary human NK cells following short term culture under hypoxia compared with normoxia and in response to interleukin 15 (IL-15) priming using a 2 x 2 factorial design. The largest contrasts observed were priming dependences for associations between hypoxia and the hypoxia-inducible factor (Hif) 1 signaling and glycolysis pathways. RT-PCR confirmed positive synergistic hypoxia/IL-15 interactions for genes of key regulatory and metabolic enzymes. IL-15 primes NK cells for effector functions, which were recently demonstrated to depend on glycolytic switching. We did not, however, observe important increases in glycolytic flux through hypoxia and priming alone. Chemical Hif-1α inhibition suggested equal importance of this transcription factor for glycolysis and energy production under normoxia and hypoxia. Hypoxia promoted secretion of CC chemokines Ccl3/4/5 and macrophage migration inhibitory factor. Unexpectedly, hypoxia also stimulated migration of NK cells through the extracellular matrix and shifted amounts of susceptible leukemia target cells toward late apoptosis in a cell killing assay. We conclude that short term hypoxia supports these activities by positively interacting with NK cell priming at the level of glycolytic gene transcription. Hypoxic conditioning of NK cells may thus benefit their use in cell-based immunotherapy of cancer.
Gesehen am 28.06.2019